The use of scaffolding-based software in developing pronunciation - Farzanfar, Anahita (2008)
This research looked at the use of a scaffolding-based software in helping learners to develop pronunciation and fluency modelled on standard American English. The study used Vygotsky’s zone of proximal development (ZPD) theory and Scaffolding Learning. Principles as a basis for observing how learners of English progressed through the learning process. Firstly, the research examined an accent-reduction software to find out how the software design supports scaffolding principles. To determine the effectiveness of the software on learners’ general pronunciation, pre-test and post-test were used. The data obtained from the pre-test and the post-test showed a significant improvement in learners’ general pronunciation after using the pronunciation learning software.Secondly, case studies were conducted to investigate Persian ESL learners’ progress in pronouncing English consonants that are absent from the phonemic inventory of Persian. The selected cases were recorded during class time, while they were working with the software. The obtained recordings were then analysed using PRAAT, a speech analysis programme. Later, two raters helped the researcher to determine the quality of the sounds produced by the learners. The results from the case study showed that with the appropriate scaffolds provided by the software, in the form of explicit instruction, native models and multimodal feedback, the learners were found to have the microgenesis improvements towards the native model and progressed within the ZPD to pronounce the consonants that were absent from the inventory system of their first language. Finally, learners’ perceptions of the software were asked in an interview session after the instructional programme. Based on their responses to the interview questions, it was found that the learners positively perceived the use of the scaffolding-based accent reduction software to improve their general pronunciation.